Screening for Drought Tolerance Within a Common Bean (Phaseolus vulgaris L.) Landrace Accessions Core Collection from the Lazio Region of Italy - Enrica Alicandri; Ester Badiani; Anna Rita Paolacci; Emilio Lo Presti; Roberta Caridi; Roberto Rea; Francesco Pati; Maurizio Badiani; Mario Ciaffi; Agostino Sorgonà (Plants)
In the present work, a subset extracted from a core collection of common beans (Phaseolus vulgaris L.) landrace accessions from the Lazio region in central Italy was used to identify the most suitable drought-tolerant or -susceptible genotypes. By applying several morpho-physiological and agronomic selection criteria recommended by the available literature, we conducted a pre-screening experiment under controlled conditions on a primary group of 24 landraces. These landraces were chosen to represent the diversity in the Lazio region in terms of geographical provenance, elevation, landform, growth habit, customary water management in the field, and native gene pool. Pre-screening under controlled conditions allowed us to identify two subsets of landraces: one exhibiting the most drought-tolerance and one showing the most susceptibility to drought. These two subsets were then tested in field trials using two water treatments, i.e., normal irrigation versus no irrigation. Such field experiments were simultaneously conducted at two sites within the Lazio region, deliberately chosen to maximize their differences in terms of pedo-climatic conditions. This notwithstanding, the core findings from the two separate field experiments were remarkably consistent and coherent among each other, highlighting a notable degree of variability within the group of the tested landraces. In general, the morpho-physiological traits considered were found to be less responsive to water shortage than yield parameters. A statistically significant Landrace × Treatment interaction was found for almost all the yield parameters considered, suggesting that certain genotypes are more susceptible than others to water shortage. By taking into account the concept of “yield stability”, i.e., the ability to maintain comparatively high yields even under conditions of water scarcity, certain common bean landraces were found to be the most promising, in terms of drought tolerance. Two genotype pairs, in particular, could be of interest for studying the morpho-physiological and molecular mechanisms underlying drought tolerance in common bean, as well as for identifying quantitative trait loci associated with water scarcity, which could be beneficially employed in breeding programs. The results reported here also suggest that pre-screening under laboratory conditions, followed by targeted field trials, can constitute a reliable, efficient, and resourceful combined approach, in which morpho-physiological traits measured on juvenile plants might play a role in predicting drought tolerance at the agronomic level.